Correlation between double-J stent length and patient body height: a randomized, prospective cohort study - Mohd Hamid Shafique Ahmed; Amandeep Arora; Pramol Hambarde; Ajit Sawant; Prakash Pawar; Asif Mulla (African Journal of Urology)
Abstract Background To evaluate the correlation between double-J (DJ) ureteric stent length and patient body height compared with direct ureteric length (DUL). Methods This randomized, prospective cohort study was conducted at a tertiary care center in the Department of Urology, Mumbai, Maharashtra, India, between January 2017 and January 2018. Male and female patients above the age of 12 years who presented with urolithiasis and required double-J (DJ) stenting following endoscopic lithotripsy (URSL, PCNL, RIRS) were enrolled in the study. In Group 1, stent selection was based on the direct ureteric length (DUL), and in the other group (Group 2), double-J ureteric stents were inserted based on the patient’s body height. All patients underwent postoperative X-ray kidney-ureter-bladder examination on day 3 to assess the graded position of the double-J (DJ). The relationship between the graded position of the double-J stents, stent compliance, and patient discomfort was evaluated at a follow-up visit 2 weeks postoperatively. Results A total of 222 patients were included in the study, with 113 patients in group 1 stented according to DUL and 109 patients in group 2 stented according to height. The mean age of the patients was 42.12 years (± 15.05), with Group 1 having a slightly longer mean DUL of 24.11 cm (± 1.27) compared to Group 2, which had a mean DUL of 23.05 (± 1.74) (P < 0.001). Group 1 exhibited a higher proportion of symptomatic patients than group 2, with a greater mean number of symptoms per patient (1.76 vs. 1.07, p = 0.0005). Group 1 also reported more severe symptoms than group 2 (2.62 vs. 2.05, p = 0.0188). The analysis revealed significant positive correlations between the DUL and both Height and weight (r = 0.316; p = 0.0001). However, no statistically significant correlations were observed between DUL, body weight, and body mass index (BMI). Conclusion Our study suggests that Height-based DJ stent selection is superior to direct DUL measurement and height as a predictor of DUL, providing means to predict DUL based on the patient’s height.